Early in-hospital discontinuation of aspirin on the first post-procedural day after percutaneous coronary stent implantation in patients on direct oral anticoagulation - von Stein, Philipp; Seitz, Lukas; Wienemann, Hendrik; Hohmann, Christopher; Baar, Till; Baldus, Stephan; Halbach, Marcel (Frontiers in Cardiovascular Medicine, 2023)
Background Previous trials investigating antithrombotic therapy with a direct oral anticoagulant (DOAC) and a P2Y12 inhibitor after percutaneous coronary intervention (PCI), termed dual therapy, allowed a short period of triple therapy including a DOAC, a P2Y12 inhibitor, and aspirin. Aims This study aimed to determine whether discontinuation of aspirin on the first post-procedural day is safe or causes ischemic events. Methods Ischemic and bleeding events during hospitalization were investigated retrospectively in all patients treated with dual therapy (DOAC + P2Y12 inhibitor, designated as group 1) or triple therapy (DOAC + P2Y12 inhibitor+aspirin, designated as group 2) from day 1 after PCI at our center. Results Of 4,564 consecutive PCI procedures, 1,059 (23.2%) had an indication for OAC. Of these, 322 met the inclusion criteria for group 1 and 62 for group 2. Baseline characteristics, CHA2DS2-VASc and HAS-BLED scores showed no relevant differences between the two groups, and the main indication for DOAC therapy was atrial fibrillation in both groups. Approximately ¼ of patients were treated for acute coronary syndrome. The mean length of post-procedural hospitalization was 2.1 ± 2.5 and 2.2 ± 3.0 days in group 1 and 2, respectively (p = 0.305). One patient per group suffered a TIA (p = 0.297). There were no other ischemic events and no statistically significant differences in bleeding events. A subgroup analysis of cases hospitalized for ≥2 post-procedural days (group 1: 100 cases, mean 4.4 ± 3.4 days vs. group 2: 25 cases, mean 4.0 ± 4.1 days) confirmed these results. Conclusion The initiation of dual therapy and thus discontinuation of aspirin on the first postprocedural day appears to be safe with respect to short-term ischemic events in a real-world population. Almost ¼ of patients undergoing PCI have an indication for OAC, highlighting the relevance of this issue.